Ground Water Governance in Kerala - Jos .C .Raphael (KILA Journal of Local Governance, 2015)
This paper intends to appraise groundwater governance issues of the Kerala State. Ground water is a common property resource and its indiscriminate exploitation by individual household users, homesteads, industries, agriculture, government drinking water & irrigation schemes etc raise serious concern. Unscientific construction of tube wells and unscientific pumping of water from these tube wells causes imbalances in aquifers and non availability of water. This affects common open dug wells which is the most important water resource of Kerala households. Government machinery is not equipped to monitor private indiscriminate drilling operations at the grassroots levels. Unqualified technical personnel of private drilling agencies and their wrong advice seem to be creating maladies in the ground water sector of Kerala. This causes social upheavals and water inequality for the common man. Much discussed multinational Plachimada Cocoa-Cola ground water extraction maladies is only the tip of the ice berg.